Les nouvelles frontières des Jeux Anthropologiques de Saint-Louis - Fabrice Delsahut (Transatlantica)
In 1904, in St. Louis, the Olympic competitions were lost in the chaos of a World Fair called the Louisiana Purchase Exposition. The Olympic Games could not escape the rise in the racist ideologies of the 20th century and they contributed to the discussing of the athletic merit of the different races. In spite of the universal spirit that was expected to prevail, the Games of St. Louis showed the racial prejudices of their organizers. They also set up special competitions, called for the occasion “Anthropological Days”, reserved for those who were considered as sub-humans by the segregationist America of that time. From these facts, we would like to show how sports sciences and burgeoning anthropology began, together, to serve such questionable causes as racial hierarchy and the right to colonize and how they greatly contributed to the birth of an American nation that put sport in the heart of its constitution. The impact of race studies on the ways of thinking sport, contrary to what the different chairmen of the IOC tried hard to make believe during the new decades, was not only a mere avatar of the Olympic movement. Finally, we shall make some forecasts regarding the influence of that interracial athletic show outside the United States that surely allowed a certain perception of otherness and limited the integration of native peoples in the world sports fabric.